Sterile syringe access and disposal among injection drug users newly enrolled in methadone maintenance treatment: a cross-sectional survey - Arnsten Julia H; McNeely Jennifer; Gourevitch Marc N (BMC, 2006)
Abstract Background We sought to assess injection practices, means of acquiring and disposing of syringes, and utilization and knowledge of harm reduction resources among injection drug users (IDUs) entering methadone maintenance treatment (MMT). Methods Interviews with 100 consecutive patients, including 35 IDUs, entering a MMT program in the Bronx, NY. Results Utilization of unsafe syringe sources was reported by 69% of IDUs in our sample. Most (80%) IDUs reused syringes, and syringe sharing was also common. Fewer than half knew that non-prescription pharmacy purchase of syringes was possible. The most common means of disposing of injecting equipment were the trash (63%) and syringe exchange programs (49%). Conclusions These findings indicate that drug users entering treatment under-utilize sanctioned venues to obtain sterile syringes or safely dispose of used injection equipment. Programs providing services to drug users should adopt a proactive stance to address the safety and health issues faced by injectors.